Fasting, adrenalectomy, and gluconeogenesis in the chicken and a carnivorous bird - Veiga, J. A. S.; Roselino, E. S.; Migliorini, R. H. (My University, 1978)
Previous studies showed that livers from carnivorous birds have a higher gluconeogenic capacity and higher levels of gluconeogenic enzymes than livers from granivorous birds. In this work we compare the effects of fasting and adrenalectomy on gluconeogenesis. Fasting in the chicken elicited increased rates of incorporation of 14C from alanine into blood glucose, increased gluconeogenesis in liver slices, and increased activities of four gluconeogenic enzymes: glucose-6-phosphatase, phosphoenolpyruvate carboxykinase, alanine aminotransferase, and aspartate aminotransferase. These responses in the chicken resemble those observed in fasted rodents. In marked contrast, fasting in black vultures induced decreased rates of incorporation of alanine label into circulating glucose, decreased gluconeogenesis in liver slices, and no change in any of the four enzymes studied. This unusual response to fasting in the carnivorous bird is probably related to the high-protein-low-carbohydrate content of the diet. Fasted adrenalectomized birds (granivorous and carnivorous) had reduced rates of in vivo glucose synthesis, decreased liver gluconeogenesis, and lower activity of glucose-6-phosphatase and aspartate aminotransferase, without change in phosphoenolpyruvate carboxykinase and alanine aminotransferase activities.
Keywords: aspartate aminotransferase; glucose 6 phosphate; phosphopyruvate carboxylase; adrenalectomy; alanine c 14; animal experiment; bird; caloric restriction; chicken; endocrine system; gluconeogenesis; liver slice; small intestine